Impact of the Covid-19 pandemic on perinatal mental health (Riseup-PPD-COVID-19): protocol for an international prospective cohort study - Motrico, Emma; Bina, Rena; Domínguez-Salas, Sara; Mateus, Vera; Contreras-García, Yolanda; Carrasco-Portiño, Mercedes; Ajaz, Erilda; Apter, Gisele; Christoforou, Andri; Dikmen-Yildiz, Pelin; Felice, Ethel; Hancheva, Camellia; et al. (My University, 2021)
Corona Virus Disease 19 (COVID-19) is a new pandemic, declared a public health emergency by the World Health Organization, which could have negative consequences for pregnant and postpartum women. The scarce evidence published to date suggests that perinatal mental health has deteriorated since the COVID-19 outbreak. However, the few studies published so far have some limitations, such as a cross-sectional design and the omission of important factors for the understanding of perinatal mental health, including governmental restriction measures and healthcare practices implemented at the maternity hospitals. Within the Riseup-PPD COST Action, a study is underway to assess the impact of COVID-19 in perinatal mental health. The primary objectives are to (1) evaluate changes in perinatal mental health outcomes; and (2) determine the risk and protective factors for perinatal mental health during the COVID-19 pandemic. Additionally, we will compare the results between the countries participating in the study.
Keywords: Anxiety; COVID-19; Coping mechanisms; Depression; Post-traumatic stress disorders; Postpartum; Pregnancy; Risk factors